Multivariable modeling and multivariate analysis for the behavioral sciences - Everitt, Brian S (Statistics in the social and behavioral sciences series (Chapman & Hall/CRC), 2010)
Multivariable Modeling and Multivariate Analysis for the Behavioral Sciences shows students how to apply statistical methods to behavioral science data in a sensible manner. Assuming some familiarity with introductory statistics, the book analyzes a host of real-world data to provide useful answers to real-life issues.<U+000d><U+000a><U+000d><U+000a>The author begins by exploring the types and design of behavioral studies. He also explains how models are used in the analysis of data.